Pembelajaran Teknik Dasar Pencak Silat Tapak Suci Untuk Ekstrakulikuler SDN 6 Bantur Kabupaten - Muhammad Syawal Nur Mansyah; Ari Wibowo Kurniawan (Cahaya Ilmu Bangsa Institute, 2024)
In the process of learning the basic techniques of pencak silat tapak suci at extracurricular SDN 6 Bantur requires the correct technique, because the results of observations show that 75% of students at extracurricular SDN 6 Bantur still have not mastered the basic techniques of pencak silat. Based on the results of the questionnaire questionnaire, there are still many extracurricular students who have not mastered the basic techniques of pencak silat, such as punching techniques, stance, posture, kicks, parries and falls. The purpose of the research is to develop the correct learning of basic pencak silat techniques for extracurricular students at SDN 6 Bantur. This research is a type of Research and Development (R&D) research using the Lee & Owens development model. The subjects tested were 15 students. Based on the data obtained by researchers based on data analysis from media experts obtained 88% results, learning experts obtained 89% results, martial arts experts obtained 90% results and field trials obtained 85% results. The results of data analysis from experts and field trials obtained